Informational and analytical support of planning processes of marketing actions in high-speed trains - E. A. Makarova; K. V. Surzhin; S. S. Morozov; S. V. Muktepavel; I. N. Spesivtseva (Вестник Научно-исследовательского института железнодорожного транспорта)
In modern conditions, the important tasks of the Directorate of High-Speed Communication of the JSC “Russian Railways” are to improve the quality of transport services, maintain stable positions in the transport market, and increase demand. The use of a set of marketing tools in “Sapsan” trains allows maintaining price accessibility of transportation and ensures the construction of long-term mutually beneficial relations with customers. Carrying out activities to stimulate demand requires the analysis of a large amount of statistical data for planning, monitoring and summarizing the marketing activities. For information support of the decision-making process on the basis of the ACS “Express-3”, a set of tasks has been developed that provides the calculation of the characteristics of passenger traffic in the segment of high-speed communication. The new functionality allows the user to receive an analysis of the passenger traffic parameters taking into account the demand parameters (age, sex, citizenship) and the conditions of the trip (class of service, availability of benefits, participation in the promotion). In the process of carrying out analytical work, it is important for the specialists of the passenger complex not only to obtain and examine traffic statistics, but also to determine the impact of marketing actions on the amount of revenue receipts. Software implementation of the relationship construction between the volumes of traffic and revenues from the sale of travel documents was carried out on the basis of the ACS “Express-3”. To determine the annual cycles of growth/decline in revenues, it is ensured that an autocorrelation function is constructed and the development trends are determined by the indicator “revenue receipts”. The functionality created on the basis of ACS “Express” is a flexible system of reports that are formed at the user's request, allowing you to view information on the structure of passenger traffic with varying degrees of detail for compiling programs to stimulate demand and analyze its effectiveness.